Empowering green transportation: strategies for electric vehicle adoption and charging infrastructure in Malaysia - Raja Ma’amor Shah, Raja Noor Farah Azura; Azmar, Nur Amira Syahirah; Mohd Azmi, Mohd Syahriman; Abd Karim, Nor Suriya; Md Husin, Nor Hafizah; Misron, Norhisam; Sri Utami, Nida (Semarak Ilmu Publishing, 2024)
An electric vehicle (EV) is a vehicle driven by an electric motor and a battery ratherthan a conventional internal combustion engine (ICE) that depends on petroleumordiesel fuel. The main objective of this paper is to provide a clear overviewof thepresent EV market, particularly in Malaysia. There are several different types of EVs, such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), batteryelectric vehicles (BEV), and fuel cell electric vehicles (FCEV). However, each of themhas its strengths and weaknesses. This paper also discusses the technical specifications and general classifications of EVs. Malaysia follows MS IEC 61851andSAE J1772 to outline the standards and procedures for conductive connectioncharging of electric vehicles. Mathematical modelling is often employed to forecast EV adoption among users. To enhance the EV adoption and alleviate transportationchallenges, strategically placing Photovoltaic Electric Vehicle Charging Stations(PEVCS) in Malaysia is crucial. Lastly, this paper discusses the progress of EVdevelopments in Malaysia and outlines the criteria required for the allocationof PEVCS.